5 Year Survival of Endoscopic ACL Reconstruction with Live Donor Hamstring Tendon Allograft in Juveniles and Adolescents. Issue 5 (31st May 2017) - Roe, Justin; Fitzgibbon, Emma; Salmon, Lucy; Cooper, Robert; Pinczewski, Leo
Introduction: ACL reconstruction with autografts in the young is associated a higher incidence of repeat injury when compared to adults. This led the authors to consider alternative graft material for the ACL deficient young population. This study was performed to assess the survival of ACL reconstruction with a living related hamstring tendon autograft in a large series of juveniles and adolescents. Aim: To determine the survival of the ACL graft and the contralateral ACL (CACL) after primary ACL reconstruction with living donor allograft in patients aged < 18 years and to identify the factors that increase the odds of subsequent ACL injuries. Methods: Patients having undergone primary ACL reconstruction with a living donor hamstring tendon allograft at age <18 years between 2005 and 2014 included in a prospective database were considered for this study. Patients completed a subjective survey involving the International Knee Documentation Committee (IKDC) questionnaire in addition to questions regarding current symptoms, further ACL injuries, family history of ACL injury, and current level of activity. Results: A total of 218 adolescents (mean age 14.7, age range, 8-17 years) met the inclusion criteria and were reviewed at a mean of 48 months after surgery. Of these, there were 51 ACL graft ruptures (23%) and 26 contralateral ACL ruptures (12%). The 1, 2 and 5 year survival of the ACL graft was 88%, 80% and 74%. The 1, 2 and 5 year survival of the contralateral ACL was 99%, 93% and 85%. Survival of the ACL graft was more favorable in those with open growth plates (93, 90, 85 at 1, 2 and 5 survival) compared to closed growth plates (86, 75, 68 at 1, 2 and 5 year survival), odds ratio 2.3 (95% CI 1.1 to 4.8, p=0.03). A return to preinjury level of activity was reported by 79%, and the mean IKDC score was 92 of a possible 100. A positive family history of ACL injury was present in 35%. Conclusion: Further injury after ACL reconstruction in the young presents a challenging problem. ACL reconstruction using a living related donor allograft is associated with high rates of return to sport and good subjective outcomes. This technique may be considered a viable option for ACL reconstruction in the young patient with open growth plates, but does not appear to reduce further injury in older adolescents.